2012
DOI: 10.1007/s12010-012-9986-z
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid-Induced Structural and Activity Changes in Hen Egg White Lysozyme

Abstract: Lysozyme crystals in the presence of 1-butyl-3-methylimidazolium tetrafluoroborate ([C(4)mim]BF(4)), 1-butyl-3-methylimidazolium chloride ([C(4)mim]Cl), 1-butyl-3-methylimidazolium bromide([C(4)mim]Br), and 1,3-dimethylimidazolium iodine([dmim]I) were prepared, and the influence of ionic liquids (ILs) on the structure and activity change of lysozyme was investigated. Fourier transform infrared spectroscopy revealed the major secondary structures of α-helix and β-sheet for lysozyme. It was interesting to note t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…However, the water removal may have positive and/or negative consequences for the protein solubility [84]. Hydrophobic ionic liquids may form two phase systems with water resulting in less depletion of water molecules from the protein surface and hence an increased protein solubility [85, 86]. …”
Section: Through the Eyes Of The Proteinmentioning
confidence: 99%
“…However, the water removal may have positive and/or negative consequences for the protein solubility [84]. Hydrophobic ionic liquids may form two phase systems with water resulting in less depletion of water molecules from the protein surface and hence an increased protein solubility [85, 86]. …”
Section: Through the Eyes Of The Proteinmentioning
confidence: 99%
“…The effect of ILs on the thermal behavior of lysozyme crystal can be related to the change interaction among lysozymes in solution. In our previous work, the influence of ionic liquids (ILs) on the structure of lysozyme was investigated by Fourier transform infrared spectroscopy and Raman spectroscopy. The study indicated that ILs can result in lysozyme structural change.…”
Section: Resultsmentioning
confidence: 99%
“…Fourier transform infrared spectroscopy revealed the major secondary structures of α‐helix and β‐sheet for lysozyme. The activity study showed that the ILs used brought a positive effect …”
Section: Introductionmentioning
confidence: 99%
“…The activity was assessed based on the ability of HEWL to break down the cell wall of Micrococcus luteus, which causes a decrease in the turbidity of bacterial cells as observed by measuring the absorbance at 450 nm. The activity of HEWL was calculated according to the report published by Dang: [53] unit mg ¼ A 450=min � 1000 mg enzyme in reaction mixture…”
Section: Hewl Activity and Renaturation In The Presence Of Various Cations And Anionsmentioning
confidence: 99%